Hubristic motivation as a self-regulation factor in primary school in the context of neuropsychological research - Nadon, Viktoriia; Fedoryk, Viktoriia; Fomenko, Karyna; Diomidova, Nataliia; Kuznietsov, Marat; Tatiievska, Mariia (LUMEN Publishing House, 2023)
The article highlights the conceptual aspects of personality motivation as an important phenomenon of human well-being achievement. During the analysis of theoretical approaches to the definition of hubristic motivation highlighted the psychological phenomenon of personality self-regulation as a manifestation of neurophysiological processes. The article presents the findings of scientists regarding motivation factors, in particular, the principle of self-regulation formation in the context of pedagogy and neuropsychology. The components of the psychological aspect of self-regulation in the context of self-awareness and determination of personality behavior, which contributes to self-realization and socialization are analyzed. In order to determine the most effective factors of personal motivation for selfdevelopment, the neurophysiological characteristics of the individual were determined. The article is based on the results of an experimental study, namely, determining the indicators of motivation to learn among primary school students as a manifestation of self-regulation in achieving success in a particular case. The study of motivation was carried out according to the Milman method. The indicators of the study became the basis for determining the effectiveness of hubristic motivation as a neurophysiological manifestation of personality. The study was conducted on the basis of the integrative method of synthesis and analysis, based on the results of the research, descriptive and scientific method of studying the basics of neuropsychology and neuropedagogy. The method of questioning was used during the research on the method of determining personality motivation. The results of the study became the basis for conclusions about the factors of self-regulation ofpersonality in elementary school as a manifestation of hubristic motivation.
Keywords: Neuropsychology; neuropedagogy; self-realization; socialization; personal self-development